MENYELESAIKAN KONFLIK PENGUASAAN KAWASAN HUTAN MELALUI PENDEKATAN GAYA SENGKETA PARA PIHAK DI KESATUAN PENGELOLAAN HUTAN LAKITAN - Gamin Gamin; Hariadi Kartodihardjo; Lala M Kolopaking; Rizaldi Boer (Jurnal Analisis Kebijakan Kehutanan, 2014)
The style of the party facing a conflict (conflict style) needs tobe known to  find an effective dispute resolution. The main actors and supporting actors and interests/role and influence or power and its relationship needs to be carefully mapped. What are the actions that can be taken to resolve the conflict based on the style of the parties is something that needs to be answered in this study. In this study conflict styles of actors assessed  using conflicts style analysis (AGATA). This study shows that the conflict-style compromise, accommodation and collaboration facilitated and mediated for proposing Village Forest, Community Forest Partnership  to obtain legal recognition on managing state forest land as well as recognizing state forest, hence the issuance of permits The Village Forest and Community Forest Partnership can be  accelerated. The role of outside parties who are not related with conflict is essential to facilitate and mediate the parties to a conflict resolution. Competing parties need  to be  mediated so his style could change to compromise, accommodation or collaboration. Even if his style would remains unchanged it  will result in a constructive option to acquire rights to the land through forest discharge process. To the avoiding-style party an  intensive communication needs to be done  in order to be aware of the conflict or change his style to compromise.